INVESTIGASI NUMERIK VIV (VORTEX INDUCED VIBRATION) PADA DIAMETER KABEL HYDROPHONE 0.04 M SISTEM AKUSTIK BAWAH AIR - Maria Margareta Zau Beu; I Putu Andhi Indira Kusuma (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
The 2D numerical simulation of an underwater acoustic system undergoing VIV (Vortex Induced Vibration) which is in position parallel to 5 m distance with variation of hydrophone cable position. The diameter of the hydrophone cable in use is 0.04 m, with Reynold numbers (Re) variations of 13000, 15000, 17000, 19000, 21000, 23000, 25000, 27000 and 30000. Position variations are used to determine the flow pattern characteristics that occur behind the cylinder as well the maximum value of drag coefficient (CD) and lift coefficient (CL). The simulation results show that the characteristic flow pattern around a cylinder at each Re value indicates the release of the vortex behind the cylinder with different drag and lift coefficient values. Keywords: Vortex Shedding, Hydrophone, Acoustic System